Notice of a 'Burgh,' Recently Opened in the Island of Burray, Orkney (Proceedings of the Society of Antiquaries of Scotland, 1856)
Details of the author's excavations of 'The Pict's Castle' on Burray reveal the dimensions and materials used in the site's construction. Mr Farrer also remarks on the finds made during the excavation, but does not speculate on the site's purpose.